Giant clam growth in the Gulf of Aqaba is accelerated compared to fossil populations. Issue 1957 (25th August 2021) - Killam, Daniel; Al-Najjar, Tariq; Clapham, Matthew
Abstract : The health of reef-building corals has declined due to climate change and pollution. However, less is known about whether giant clams, reef-dwelling bivalves with a photosymbiotic partnership similar to that found in reef-building corals, are also threatened by environmental degradation. To compare giant clam health against a prehistoric baseline, we collected fossil and modern Tridacna shells from the Gulf of Aqaba, Northern Red Sea. After calibrating daily/twice-daily growth lines from the outer shell layer, we determined that modern individuals of all three species ( Tridacna maxima, T. squamosa and T. squamosina ) grew faster than Holocene and Pleistocene specimens. Modern specimens also show median shell organic δ 15 N values 4.2‰ lower than fossil specimens, which we propose is most likely due to increased deposition of isotopically light nitrate aerosols in the modern era. Nitrate fertilization accelerates growth in cultured Tridacna, so nitrate aerosol deposition may contribute to faster growth in modern wild populations. Furthermore, colder winter temperatures and past summer monsoons may have depressed fossil giant clam growth. Giant clams can serve as sentinels of reef environmental change, both to determine their individual health and the health of the reefs they inhabit.